Application of BFOA in Two Area Load Frequency Control - Sri Krishna Sarath, P; Swetha Monica, I (International Journal of Engineering and Technology, 2018)
This paper Â Â presents Bacterial foraging optimization algorithm which is based on food searching process of Escherichia coli bacteria, which is gaining popularity due to its effectiveness and providing solution to real world optimization problems .BFOA is applied to control the parameter optimization of load frequency controller for tuning the parameters of the proportional integral and derivative controller. A simple two area system with thermal-thermal generating units is considered for simulation study which is controlled with PID controller. The main objective of this work is to design the controller by minimizing objective function .simulation studies demonstrate that our proposed controller is effective and transients are suppressed predominantlyÂ Â